New Perspectives in American Jewish History : A Documentary Tribute to Jonathan D. Sarna - Zola, Gary Phillip; Raider, Mark A. (Book collections on Project MUSE., 2021)
""New Perspectives in American Jewish History: A Documentary Tribute to Jonathan D. Sarna," compiled by Sarna's former students, presents heretofore unpublished, neglected, and rarely seen historical records, documents, and images that illuminate the heterogeneity, breadth, diversity, and colorful dynamism of the American Jewish experience"--